The implicit Res Judicata and the Right of Defense - Apolín Meza, Dante Ludwig (2015)
This article presents the analysis of the concept of the “implicit res judicata” and what problems it generates. To do this, the author analyzes what is traditionally understood by “objective limits” of “res judicata” and, from this; the true scope of the concept of “res judicata” implicitly will be established.